Mindset regarding mathematical ability in K‐12 teachers. (9th April 2021) - Willingham, James C.; Barlow, Angela T.; Stephens, D. Christopher; Lischka, Alyson E.; Hartland, Kristin S.
Abstract: Two potentially impactful conceptions of mathematics and mathematics teaching, teachers' implicit theories (i.e., mindset) toward intelligence and mathematical ability, have not been well examined in the literature. This study established baseline characteristics for these constructs across grades K‐12 teachers through a survey of background and mindset characteristics of 583 classroom teachers. Analyses regarding the uniqueness of these constructs, their proportions in the sample of teachers, and differences in mindset by subject and grade level taught are provided. Mindset regarding mathematical ability was found to be distinguished from mindset regarding general intelligence, and as a whole, teachers displayed drastically different distributions of mindset than the population, with growth‐oriented mindset characteristics for intelligence and mathematical ability greatest among elementary teachers and mathematics teachers. Additionally, teachers' mindsets regarding these constructs appeared to be strongly oriented toward growth. Mindset constructs, which are potentially impactful to mathematical teaching practices, should be further examined in relation to effective classroom teaching, particularly at the elementary level, and differences in the distribution of these constructs by grade level taught should be further explored.